Simultaneous phosphorus and nitrogen removal using aluminum based water treatment residual - Liang, Qian, author; Carlson, Kenneth, advisor; Davis, Jessica, committee member; Sharvelle, Sybil, committee member (Colorado State University. Libraries, 2011)
In this study, an aluminum-based water treatment residual (Al-WTR) from a local water treatment facility was investigated for its capacity for phosphorus (P) and nitrogen (N) removal in wastewater. Characterization results indicated that Al-WTR had a high content of amorphous aluminum hydroxide, which is able to bond phosphorus in solution mainly via ligand exchange. Also, Al-WTR was found to be rich in bio-available carbon, which can facilitate biological denitrification for N removal. Batch equilibrium tests analyzed the P sorption parameters according to Langmuir and Freundlich isotherms. The results of the maximum sorption capacity were 4.498, 3.258 and 2.038 g/kg at pH values of 4, 7, and 9 respectively, indicating that P sorption was favored at lower pH conditions. However, the sorption capacity results may not reflect that in continuous-flow conditions. Al-WTR was shown to be a more effective sorbent for orthophosphate phosphorus (ortho-P) than total phosphorus (TP), but still had promising removals (greater than 90%) to both. Simultaneous P and N removal in wastewater was tested in column experiments in a continuous-flow mode. 95.9% removal of ortho-P and 90.0 % removal were achieved. Also, NO3- removal was highly efficient (99.6%). In sum, using Al-WTR as a P and N mitigation agent is a feasible and sustainable technology, and could be applied in P and N control practices in point-sources and non-point sources.
Keywords: nitrogen; nutrient control; phosphorus; water treatment residual